Enucleation of a Giant Hemangioma of Liver: Old School Revisited - Karpagavel ChandraBose; A. Ramanujam; Yega Muthu (Case Reports in Surgery)
Hemangiomas are the most frequent benign hepatic tumours and are usually found in patients aged between 40 and 60 years, more frequently in women. In 30–35% of patients, the lesions are multiple. If the lesions are larger than 4–10 cm, they are coined as “giant” hemangioma. Here, we present a case of giant hemangioma treated with enucleation of the lesion and the advantages of the procedure.